Exome-first approach identified novel INDELs and gene deletions in Mowat-Wilson Syndrome patients - Gosso, Maria Florencia (2018)
Mowat-Wilson syndrome (MWS) is characterized by severe intellectual disability, absent or impaired speech and microcephaly, with a gradual post-natal onset. The syndrome is often confused with other Angelman-like syndromes (ALS) during infancy, but in older children and adults, the characteristic facial gestalt of Mowat–Wilson syndrome allows it to be distinguished easily from ALS. We report two cases in which an exome-first approach of patients with MWS identified two novel deletions in the ZEB2 gene ranging from a 4 base deletion (case 1) to at least a 573 Kb deletion (case 2).